Children performing identical gestures - Unknown:::Creator::::::::::::
Photograph is from a contact sheet and shows a group of boys and girls all standing up and trying to make the same gestures. They have one arm raised with that hand made into a fist. The other arm is across their torsos with that hand pointing to themselves.